Unsolvable problems of justice and artificial intelligence - Мišić, Marica (Glasnik Advokatske komore Vojvodine, 2025)
SummaryThe history of philosophical (and legal-philosophical) thought shows us that justice as a principle cannot be determined substantively, i.e. that there is mostly agreement that justice is something to strive for, but that, on the other hand, justice as a supreme or absolute principle cannot be substantively to describe. Some middle way born from the relativity and changeability of the content of justice and its absoluteness as a form is the concept of procedural justice or the internal morality of law - mainly the procedural requirements that the regulation must satisfy in order to be valid as law. Lawyers who, as Kant and many authors following Kant often apostrophize, have not yet found their concept of law, new challenges are posed by the development of modern technology and the application of artificial intelligence in many areas, as well as in certain domains of law. From dilemmas related to the ethics and legal regulation of artificial intelligence, to questions concerning the possibility of applying artificial intelligence in the process of creating, interpreting and applying law, solutions to the challenges that are the task of contemporary scientific thought and ethical and legal practice may be of importance for the future. rights. The paper will, among other things, consider the possibility of achieving justice in the context of the use of artificial intelligence in the process of creating, interpreting and applying law, with regard to the thesis of the insufficiency of the explanation and realization of justice with juspositivist understandings of justice.
Keywords: Key words: justice, value, legal certainty, equality, artificial intelligence